Preferential feeding and damage to cultivars of Nigerian cassava by the variegated grasshopper (Zonocerus variegatus) - Terry, E.R.; Schaefers, G.A.; Garber, M.J. (1977)
Large populations of Zonocerus variegatus invaded a cassava crop established during the dry season. The resultant damage was severe, certain cultivars being totally destroyed. The grasshoppers exhibited a statistically significant preference for certain cultivars the defoliation of which shifted attacks to less preferred ones. On a particular variety (Isunikankiyan), populations increased and persisted even after defoliation, probably due to acceptability of the bark by the grasshopper